Perbandingan Metode Simple Additive Weighting Dan Metode Composite Performance Index Dalam Sistem Pendukung Keputusan Kelayakan Bantuan Pupuk Subsidi Untuk Kelompok Tani - Rahmat Hidayat; Yupianti Yupianti; Devi Sartika (Jurnal Media Infotama, 2025)
Decision Support System (SPK) is a system used to assist decision making in an organization or company. The development of a decision support system with the Simple Additive Weighting (SAW) method and the Composite Performance Index (CPI) method to determine the beneficiaries in determining the distribution of fertilizer assistance to farmer groups, and can minimize the inaccuracy in distributing the fertilizer assistance by applying the Simple Additive Weighting method and the Composite Performance Index method. This system is expected to help the government to determine the right recipient of fertilizer assistance, and be able to provide accurate and consistent recommendations, and increase transparency in the selection process. With this system, it is expected that the process of providing subsidized fertilizer assistance can run more fairly, efficiently, and on target.